A policy support framework for the balanced development of economy-society-water in the Beijing-Tianjin-Hebei urban agglomeration. (10th November 2022) - Hao, Lingang; Yu, Jingjie; Du, Chaoyang; Wang, Ping
Abstract: Balancing socioeconomic development with water resources among cities is critical for the sustainable development of urban agglomerations. Despite this urgent need to analyse balanced development, a recognized method to measure and improve the balanced degree in urban agglomerations impacted by water resource constraints is still lacking. This study proposes a framework to evaluate the balanced development degree and simulate the impacts of interactions and management policies of economy-society-water on balanced development in urban agglomerations. This paper establishes a balanced development degree index using the coupling coordinated degree (CCD) model; constructs a system dynamic (SD) model to simulate economy-society-water interactions; and designs future scenarios to evaluate the impacts of industry, population, water, and comprehensive regulation policies on balanced development. The integrated framework that couples the above three methods was validated in the Beijing-Tianjin-Hebei (BTH) region in China. The results showed that (a) industrial and population regulations slightly increase the level of balanced development by 0.0025 and 0.0024 in the BTH region but will increase water scarcity in Hebei; (b) improving water use efficiency is an effective way to relieve water stress; and (c) the balanced degree increases by 15% under comprehensive regulatory policies. Integrated water-economy-society management makes it possible to achieve co-development without increasing the water crisis in the BTH region. This study provides support for policy-makers and promotes sustainable development of the water-economy-society in urban agglomerations. Graphical abstract: Image 1 Highlights: A framework for balancing urban agglomerations under water constraints is developed. An index of urban agglomerations balanced development is established. Efficiency of the proposed approach is examined in the Beijing-Tianjin-Hebei region. The water system is key to balanced development in the Beijing-Tianjin-Hebei region.